Pengaruh Motivasi Kerja dan Iklim Madrasah Terhadap Kemampuan Guru dalam Mengimplementasikan Kurikulum 2013 - Nyayu Khodijah; Mardiah Astuti; Sriwati Sriwati (Studia Manageria, 2021)
. This study analyzes and examines the effect of work motivation and madrasah climate on the ability of teachers to implement the 2013 curriculum at MA Ar Risalah Sungai Lilin Musi Banyuasin. A quantitative research approach with this type of explanatory research research. As for the research technique using an instrument in the form of a questionnaire, the research respondents were 18 teachers at MA Ar Risalah. The data collection technique used a questionnaire and then analyzed using product moment correlation for partial testing and multiple linear regression for simultaneous testing. The research results reveal several important findings. First, the findings show that there is a positive influence between work motivation and the ability of teachers to implement the 2013 curriculum, with a percentage of 28.3%, it is concluded that the higher the work motivation, the higher the teacher's ability to implement the curriculum. Second, it shows a positive influence between the madrasah climate and the teacher's ability with a percentage of 30.5%. The better the madrasah climate, the higher the teacher's ability to implement the 2013 curriculum. Third, it shows a positive influence between work motivation and madrasah climate, on The teacher's ability to implement the 2013 curriculum, the amount of influence is 58.8%. The results of the analysis show that work motivation and madrasah climate jointly affect the achievement of teachers' abilities in implementing the 2013 curriculum. Keywords: Work Motivation, Madrasah Climate, and the ability of teacher.